The New Orleans levee failure - Huddleston, Emma (Engineering disasters (Core Library (Firm)), 2020)
Explores how and why the levees of New Orleans failed and caused devastating flooding during Hurricane Katrina in 2005, and also how the city has spent lots of money to build better, safer levees for today. Includes a glossary.